Emerging Techniques in Degenerative Thoracolumbar Surgery. Issue 3 (21st February 2017) - Choma, Theodore J.; Mroz, Thomas E.; Goldstein, Christina L.; Arnold, Paul; Shamji, Mohammed F.
Abstract: There continue to be incremental advances in thoracolumbar spine surgery techniques in attempts to achieve more predictable outcomes, minimize risk of complications, speed recovery, and minimize the costs of these interventions. This paper reviews recent literature with regard to emerging techniques of interest in the surgical treatment of lumbar spinal stenosis, fusion fixation and graft material, degenerative lumbar spondylolisthesis, and thoracolumbar deformity and sacroiliac joint degeneration. There continue to be advances in minimal access options in these areas, although robust outcome data are heterogeneous in its support. The evidence in support of sacroiliac fusion appears to be growing more robust in the properly selected patient.